The Forbidden Reward. The Emergence of Parent-Child Conflicts About Food Over Time and the Influence of Parents' Communication Strategies and Feeding Practices - Spielvogel, Ines; Naderer, Brigitte; Binder, Alice; Matthes, Jörg (Frontiers in Public Health, 2021)
One of the most critical arenas for conflicts between parents and their children relates to food. Although parent-child conflicts about food are a real occurrence, this form of parent-child interaction has been rarely examined. Given the special role of parents in shaping children's diet, we especially focus on the impact of parental measures. This study investigates how parental communication strategies (i.e., active vs. restrictive) and feeding practices (i.e., overt control vs. covert control) affect the emergence of parent-child conflicts about food over time. Based on previous research, we assessed overt control through parents' use of food as a reward and restriction of their children's access to specific food types. We explored the impact of our predictors on both conflicts about unhealthy and healthy food with a two-wave panel study including parents and their children (N = 541; children aged between 5 and 11) in Austria between fall 2018 and spring 2019. Results of two multiple linear regressions indicated that predominantly parents' use of unhealthy food as a reward is connected to both healthy and unhealthy food conflicts. Furthermore, inconsistent parental educational styles increased the respective conflict potential. Active food-related mediation and covert control did not relate to food-related conflicts about unhealthy and healthy food. Parents' increased use of overtly controlling and restrictive feeding practices might not be only counterproductive for children's diet but also for food-related parent-child interactions. Instead, a “health discourse” (i.e., active food-related mediation) might prevent food-related conflicts and foster a healthy growth in the future.